Characteristics and 1-year prognosis of non-obstructive acute coronary syndrome. (26th April 2021) - Viegas, JM; Goncalves, AV; Cardoso, I; Rosa, SA; Timoteo, AT; Ferreira, RC
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Among patients admitted at catheterization laboratory with suspicion of acute coronary syndrome (ACS) a minority have no obstructive epicardial coronary disease (MINOCA).  The characteristics and outcomes of this subgroup remains unclear. Purpose: The aim of the present study is to characterize MINOCA patients and assess the 1-year prognosis regarding total mortality. Methods: A standardized registry was prospectively performed for all ACS patients admitted in a single tertiary care centre during a ten-year period. Patients were divided according to have at least one obstructive coronary artery (G1), defined by a stenosis above 50%, or not (G2) and baseline characteristics were compared between the two groups. All-cause mortality at 30 days and at 1 year were also compared using univariate Cox analysis. Results: From 3765 ACS patients admitted during the study period, 461 (12.2%) were included in G2. G2 patients were older (62.6 ± 13.1 vs 66.2 ± 13.7; p < 0.001) and more frequently women (26.3% vs 44.2%; p < 0.001). Smoking was more frequent in G1 (40.0% vs 21.9%; p < 0.001) but the prevalence of hypertension was higher in G2 (55.2% vs 64.2%; p < 0.001). There were no differences regarding dyslipidaemia and diabetes. End-stage chronic kidney disease was higher in G2 (2.4% vs 4.1%; p = 0.025). Regarding the clinical evolution during hospitalization, G2 presented more frequently with Killip-Kimball class ≥II (13.9% vs 19.3%; p = 0.001), but at release there was no difference in the proportion of patients with left ventricular ejection fraction ≤50% (34.8% vs 32.1%; p = 0.286).  ACS with ST-segment elevation was more common in G1 (58.8% vs 52.1%; p = 0.006), but no differences were found regarding left and right bundle branch block patterns at presentation. In-hospital and 30-day mortality was not significantly different between groups (5.9% vs 7.4%; p = 0.205). However, at 1-year follow-up, G2 had a worse outcome regarding total mortality (HR (95%CI); 1.473 (1.103-1.969); p = 0.008, figure 1). Conclusion: MINOCA patients seem not to be a low-risk group of ACS patients, since in this study they had a higher 1-year mortality than ACS patients with obstructive coronary disease. This higher mortality only became apparent after 30 days from the ACS. A systematic diagnostic work-up for further implementation of the most appropriate treatment should be crucial for getting better outcomes with this group of patients.